Burden and trends of multiple sclerosis in China from 1990 to 2019: a systematic analysis for the Global Burden of Disease Study 2019 - Min Li; Hua Zhong; Rong Jiang; Na Zhou; Shengnan Duan; Ni Yuan (BMJ Open)
Objective To compare the burden of multiple sclerosis disease indicators in the Asia-Pacific countries, China and globally through the Global Burden of Disease 2019 (GBD2019) Database, and to analyse the changes of multiple sclerosis disease burden in China from 1990 to 2019.Study design Observational study based on the Global Burden of Disease.Setting The relevant incidence, prevalence, death and disability-adjusted life year (DALY) rates and corresponding age-standardised rates (ASRs) and sociodemographic index (SDI) in China, globally and in Asia-Pacific countries were extracted from the GBD2019 Database to further study the age-standardised incidence, prevalence and mortality, and the relationship between DALY rate and SDI.Results Various disease burden indicators of multiple sclerosis in China are at low level in the world, and the prevalence, incidence and DALY rates have slowly increased from 1990 to 2019. During this period, the age-standardised prevalence rate (ASPR) of multiple sclerosis in China showed an upward trend, while the age-standardised death rate (ASDR), age-standardised DALY rate (ASR-DALY) and age-standardised incidence rate all decreased to varying degrees, which were roughly consistent with the global amplitude changes, and all indicators are similar to most countries in the Asia-Pacific region. As the value of the SDI increases, the ASPR of multiple sclerosis was trending upward, and the ASDR was trending downward.Conclusion Compared with other countries in the Asia-Pacific region, China is in a low state of disease burden indicators. However, as a developing country and the most populous country in the world, the total number of patients is not small, and as a rare disease, the treatment cost is relatively expensive, and the treatment cost of the complications caused by the disease is not low. The construction of the medical security system should be strengthened to reduce its burden on individuals, families and society.